What's integrity got to do with it? Second-year experiences of the Path2Integrity e-learning programme - Noémie Hermeking; Julia Priess-Buchheit (Canadian Science Publishing, 2022)
Organisations in Europe differ significantly in how they promote research integrity (RI). Higher education institutions play a pivotal role in disseminating a culture of RI and responsible conduct of research (RCR). Adhering and strengthening mentoring systems, implementing codes of conduct, and raising awareness are just a few initiatives among many to enhance students' training in RCR. This article describes the Path2Integrity Learning Card (P2LIC) programme, a proactive training programme to foster RI. This programme was further developed in 2020 and the updated feedback loops took place in four countries (Germany, Denmark, Spain, and Poland). We outline the P2ILC development and final design, the trainer feedback on the programme from the second year of operation, and suggest future considerations for RCR training to strengthen research integrity.